Phytoplankton and Physicochemical Analysis on the Water System of the Temperate Estuary in South America:Bahía Blanca Estuary, Argentina - Guinder, Valeria Ana (2012)
Under the contemporary scenario of global climate change and increasing coastal eutrophication, baseline studies of phytoplankton diversity and distribution in relation to habitat conditions constitute the first approach to evaluate potential shifts at the base of the food webs. Here we present data of phytoplankton species composition and environmental variables in winter 2006 in a temperate estuary in South America, Argentina. The results showed that the Bahía Blanca Estuary is markedly turbid (particulate suspended matter up to 60 mg L-1) with high nutrient concentrations. Apparently, besides high light attenuation coefficients (k up to 2.7 m-1), the combination of a shallow (~7 m depth) and well mix water column in the innermost zone of the estuary allows light penetration (mean light intensity in the mixed zone Im 57.8 μEm-2s-1 and euphotic zone to mixed zone ratio Zeu:Zm over 0.2), intensive nutrient regeneration and eventually phytoplankton massive growth (up to 1.8 x 106 cells L-1). Moreover, the relatively low residence time and the low river runoff seem to promote the accumulation of nutrients and phytoplankton biomass in the head of the estuary. Anthropogenic activities and autochthonous production are responsible of high particulate organic matter loads (8.3 ± 1.5 mg L-1). Diatoms appeared as the dominant group in winter with the emergence of Cyclotella aff. choctawatcheena (5-15 μm) as the dominant species (up to 82 % of the total phytoplankton abundance). The distribution and habitat preferences of this diatom are briefly discussed in relation to the pelagic environment in the Bahía Blanca Estuary.